A Broad-Spectrum Antimicrobial Activity of Bacillus subtilis RLID 12.1 - Ramya Ramachandran; Ajay Ghosh Chalasani; Ram Lal; Utpal Roy (The Scientific World Journal)
In the present study, an attempt was made to biochemically characterize the antimicrobial substance from the soil isolate designated as RLID 12.1 and explore its potential applications in biocontrol of drug-resistant pathogens. The antimicrobial potential of the wild-type isolate belonging to the genus Bacillus was determined by the cut-well agar assay. The production of antimicrobial compound was recorded maximum at late exponential growth phase. The ultrafiltered concentrate was insensitive to organic solvents, metal salts, surfactants, and proteolytic and nonproteolytic enzymes. The concentrate was highly heat stable and active over a wide range of pH values. Partial purification, zymogram analysis, and TLC were performed to determine the preliminary biochemical nature. The molecular weight of the antimicrobial peptide was determined to be less than 2.5 kDa in 15% SDS-PAGE and in zymogram analysis against Streptococcus pyogenes. The N-terminal amino acid sequence by Edman degradation was partially determined to be T-P-P-Q-S-X-L-X-X-G, which shows very insignificant identity to other antimicrobial peptides from bacteria. The minimum inhibitory concentrations of dialysed and partially purified ion exchange fractions were determined against some selected gram-positive and gram-negative bacteria and some pathogenic yeasts. The presence of three important antimicrobial peptide biosynthesis genes ituc, fend, and bmyb was determined by PCR.